PENGEMBANGAN KARYA DEKORASI RUANGAN BERMATERIAL BAMBU DENGAN INSPIRASI SIMBOL FLORA DAN FAUNA KALIMANTAN - Setiani Miftahul Hidayah; Musdalifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a bamboo-based interior decorative design inspired by the flora and fauna of Kalimantan in order to produce creative decorative works while representing local cultural values. The research employed a Research and Development (R&D) approach consisting of several stages, including analysis, design planning, prototype development, implementation, and evaluation. Data were collected through literature review, observation of the development process, visual documentation, and questionnaires distributed to respondents. The data were analyzed using qualitative descriptive analysis to examine the aesthetic, functional, and cultural representation aspects, and quantitative analysis through percentage calculations of assessment scores obtained from trained respondents and expert validators. The results indicate that the developed bamboo decorative design successfully integrates modern aesthetic elements with the representation of Kalimantan’s distinctive flora and fauna, particularly the giant moon orchid (Phalaenopsis gigantea). Based on the evaluation results, the feasibility level of the developed product reached 92.78% from trained respondents and 96.11% from expert respondents, both of which fall into the “very feasible” category. These findings suggest that bamboo, as a local and sustainable material, has considerable potential to be further developed in contemporary interior decoration while simultaneously supporting the preservation and visual representation of regional cultural identity.